2014
DOI: 10.1002/cssc.201402574
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible‐Light Photocatalytic H2 Production by ZnxCd1−xS Modified with Earth‐Abundant Nickel‐Based Cocatalysts

Abstract: The application of various earth-abundant Ni species, such as NiS, Ni, Ni(OH)2 , and NiO, as a co-catalyst in a Znx Cd1-x S system for visible-light photocatalytic H2 production was investigated for the first time. The loading of Ni or NiS enhanced the photocatalytic activity of Znx Cd1-x S because they could promote the electron transfer at the interface with Znx Cd1-x S and catalyze the H2 evolution. Surprisingly, Ni(OH)2 -loaded Znx Cd1-x S exhibits a very high photocatalytic H2 -production rate of 7160 μmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(73 citation statements)
references
References 55 publications
1
71
0
1
Order By: Relevance
“…In addition to sulfides and phosphides, several Ni-based oxides and hydroxides, such as NiO, NiO x and Ni(OH) 2 , are also well-known as highly active cocatalysts after being integrated with semiconductors for photocatalytic H 2 production [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77], as summarized in Table 3. For example, Chen et al showed that in situ photodeposition of NiO x on CdS could enhance its photocatalytic H 2 generation activity [63].…”
Section: Ni-based Oxides and Hydroxide Cocatalysts For H 2 Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to sulfides and phosphides, several Ni-based oxides and hydroxides, such as NiO, NiO x and Ni(OH) 2 , are also well-known as highly active cocatalysts after being integrated with semiconductors for photocatalytic H 2 production [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77], as summarized in Table 3. For example, Chen et al showed that in situ photodeposition of NiO x on CdS could enhance its photocatalytic H 2 generation activity [63].…”
Section: Ni-based Oxides and Hydroxide Cocatalysts For H 2 Evolutionmentioning
confidence: 99%
“…In a recent example, Ran et al compared the different activities of various Ni-based materials (i.e. NiS, Ni, Ni(OH) 2 , and NiO) as cocatalysts in combination with Zn x Cd 1−x S for visible-light-driven H 2 production [73]. It has been revealed that the types of the cocatalyst could strongly influence the photocatalytic activity of Zn x Cd 1−x S. Among various cocatalysts investigated, Ni(OH) 2 -loaded Zn x Cd 1−x S composite photocatalysts displayed the highest activity due to the synergetic effect between Ni(OH) 2 and metallic Ni formed by in situ photoreduction of a certain percentage of Ni 2+ in Ni(OH) 2 , achieving a H 2 -production rate as high as 7160 mol h −1 g −1 and a QE of 29.5% at 420 nm using TEOA as a sacrificial electron donor.…”
Section: Ni-based Oxides and Hydroxide Cocatalysts For H 2 Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] However,the scarcity and high costs of these noble-metal-based cocatalysts have hindered their application on al arge scale.T hus,t he design and development of non-noble water splitting cocatalysts with high efficiencyish ighly desired. [37] …”
Section: Surface Cocatalystsmentioning
confidence: 99%
“…4d). This photocorrosion is very common for many oxides, nitride and sulfides semiconductor photocatalysts, involving ZnO [43,44], CdS [45,46], Zn x Cd 1-x S [47], TaON [48]; and similar strategies, such as composites with graphene, more suitable sacrificial agent, surface coating protection, will be adopted to enhance photocatalytic stability of supramolecular NSs.…”
mentioning
confidence: 99%